The effect of acute blood loss complicated by limb ischemia-reperfusion on the induction of the apoptosis of pulmonary leukocytes and its correction by carbacetam - Stakhiv, O. V.; Hudyma, A. A. (Journal of Education, Health and Sport, 2020)
The development of acute lung injury is one of the severe complications of massive blood loss. Under these conditions, the apoptosis which is identified as an informative marker of the severity of the pathological process, enhances in the pulmonary leukocytes. The effect of limb ischemia and its reperfusion on the systemic mechanisms of the pathogenesis of acute massive blood loss, in particular the level of apoptosis of pulmonary leukocytes, remains understudied. There are no data concerning the efficacy of the carbacetam under these conditions. The objective of the research: to establish the effect of acute blood loss complicated by limb ischemia-reperfusion on the induction of the early apoptosis of pulmonary leukocytes and the efficacy of the carbacetam in the correction of identified abnormalities. Material and methods. The experimental studies were conducted on 216 white non-linear male rats weighing 200-220g. All procedures were carried out under thiopental sodium anesthesia. A limb ischemia-reperfusion, an acute blood loss as well as a combination of these lesions were carried out in the experimental groups. The identified abnormalities were corrected with carbacetam in the separate experimental group. After 1 and 2 hours as well as 1, 7, and 14 days, the bronchoalveolar lavage fluid of experimental animals was taken for the detection of the level of early apoptosis in the leukocyte population. The results. The simulations of a limb ischemia-reperfusion, an acute blood loss, and a combination of these lesions create the preconditions for the enhancement of early apoptosis of pulmonary leukocytes obtained from the bronchoalveolar lavage fluid. If under the conditions of simulating, solely, the limb ischemia-reperfusion the index is significantly higher than the control after 1 hour, 2 hours, and 1 day, and returns to the control level after 7-14 days, then after simulation an acute blood loss and its complication by limb ischemia-reperfusion the index is statistically significantly higher than control level at all observation periods. It has been established that the combination of massive acute blood loss and limb ischemia-reperfusion is accompanied by statistically significantly great increase in the studied parameter, as compared to the other experimental groups. The index statistically significantly decreases in all experimental groups under the effect of the carbacetam, which indicates the marked proapoptotic effect of the medication. Notwithstanding that studied parameters do not reach the level of the control group, the carbacetam is considered to be the promising medication for the correction of acute lung injury under conditions of acute blood loss complicated by limb ischemia-reperfusion. Conclusions. The simulation of a limb ischemia-reperfusion, an acute blood loss, and a combination of these lesions create the preconditions for the enhancement of early apoptosis of pulmonary leukocytes obtained from the bronchoalveolar lavage fluid. The complication of acute blood loss by limb ischemia and reperfusion is followed by statistically significantly greater abnormalities at all observation periods. Administration of the carbacetam leads to decrease in the level of early apoptosis in the bronchoalveolar lavage leukocytes after 7-14 days, which indicates the prospects of the medication for correction of identified abnormalities.